OUT-OF-POCKET HEALTHCARE PAYMENTS AND IMPOVERISHMENT AMONG MIGRANT ADOLESCENT FEMALE HEAD PORTERS IN GHANA: A CROSS SECTIONAL STUDY - Alatinga, K. A.; Kanmiki , E. W.; Abiiro, G. A. (UDS International Journal of Development, 2022)
Direct out-of-pocket (OOP) payments for healthcare can have devastating effects on vulnerable populations leading to impoverishments. Ghana’s National Health Insurance Scheme (NHIS) aims to remove financial hardships associated with seeking healthcare. However, there are concerns that vulnerable sections of the population still face healthcare-related financial hardships. This paper examines the impoverishing effects of OOP healthcare payments and the determinants of impoverishment due to OOP healthcare payments among migrant adolescent female head porters aged 10-19 years in Ghana. A quantitative cross-sectional survey was administered to a sample of 336 respondents who reported ill and sought healthcare within the last 12 months, January-December 2015, prior to the survey in 2016. Impoverishment due to OOP payment was assessed by computing the net income after payment for health care using the World Bank’s poverty line of income of $1.90 a day converted to 2015 purchasing power parity (PPP) equivalence for Ghana. The results illustrate that poverty incidence increased from 23 percent before OOP payment to 76 percent post OOP payment for healthcare. In a multivariate analysis, primary education [AOR=0.32, 95%CI=0.15-0.68]; Mamprusi (AOR=0.41, 95%CI=0.19-0.87) and other ethnic groups [AOR=0.33, 95%CI=0.14-0.75] compared to Dagomba; >1year in head portage (AOR=0.46; 0.23 - 0.95); drug store (AOR=0.43, 95%CI=0.19 - 0.96) and home treatment [AOR=0.20, 95%CI=0.05-0.85] were significantly associated with lower odds, whilst never registering for (AOR=4.05; 95%=1.82 - 9.03) or no valid NHIS card (2.29; 95%CI=1.08 - 4.83), Kumasi city [AOR=5.14; 95% CI:2.45-10.77] and severity of illness[AOR=2.86, CI 1.49-5.45] were associated with higher odds, of impoverishment due to OOP payment.. We recommend that the Ministries of Gender, Children and Social Protection and Health should collaborate to enrol adolescent female head porters onto the NHIS in order to increase their financial risk protection. Government should also put in place policy interventions including skills training and livelihood programmes to increase income levels, and improve the poverty situation of adolescent girl head porters. Key Words: Impoverishment, out-of-pocket healthcare payments, adolescent girls, migrants, Ghana